Management of a mixed overdose of calcium channel blockers, β-blockers and statins. (6th June 2014) - Thakrar, Reena; Shulman, Rob; Bellingan, Geoff; Singer, Mervyn
Abstract : We describe a case of extreme mixed overdose of calcium channel blockers, β-blockers and statins. The patient was successfully treated with aggressive resuscitation including cardiac pacing and multiorgan support, glucagon and high-dose insulin for toxicity related to calcium channel blockade and β-blockade, and ubiquinone for treating severe presumed statin-induced rhabdomyolysis and muscle weakness.